(3fHPI ef OjhGf GdUQUQjs - (3jMji Hf jhSa Hf jMji GdCfUGQj, GdUQUQj, LeGd GdOjf CHh RcQjG,J (B656 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe jeOM QShd Gddg Udi Gddg Ydjg hSde(B: (3Yf Cjef GdSaM HGdMei YQoH Hjf aDGOj hHjfge fSoH s
(3BNQgG (B:s
(3ebGHdI BHGDg hCegGJg eHQCI ef aGVMGJ GdeKGdH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B236 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B523s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B126 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B797s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs